A Woman's Calling (London : National Association of Local Government Officers)
1937 1937 1930s 13 pages APPENDIX NATIONAL ASSOCIATION OF LOCAL GOVERNMENT OFFICERS Scheme for Recruitment, Training and Promotion in the Nursing and Public Health Services of Local Government [Diagram] 292/54.73/2/1